Growth Properties And Bioactivities Of Lactobacilli In Soymilk Supplemented With B-Vitamins And Upon Physical Treatments - Ewe, Joo Ann (2013)
The growth characteristics, bioactive potential and bioconversion of isoflavones in soymilk supplemented with B-vitamins of Lactobacillus acidophilus BT 1088, L. fermentum BT 8219, L. acidophilus FTDC 8633 and L. gasseri FTDC 8131 were evaluated. The effects on the growth properties were strain- and B-vitamin- dependent. The growth was increased to a viable count exceeding 7 log10 CFU/mL. Supplementation of B-vitamins increased the α-galactosidase specific activities, thus enhanced the hydrolysis of soy oligosaccharides and substantially higher production of lactic and acetic acids after fermentation. Higher proteolytic activities also led to production of lactobacilli-fermented B-vitamin-supplemented soymilk with higher ACE-inhibitory activities. The β-glucosidase specific activities that enhanced the accumulation of isoflavone aglycones upon supplementation were also increased.